Behavioral characteristics of capsaicin mediated cutaneous, myogenic, and arthrogenic orofacial nociception in rats. (August 2018) - Rohrs, Eric L.; Neubert, John K.; Caudle, Robert M.; Allen, Kyle D.
Highlights: Behavior was assessed in rats following capsaicin application. Tactile allodynia and gnawing behavior were investigated. Cutaneous, myogenic and arthrogenic nociception were investigated. Cutaneous and myogenic nociception models displayed tactile allodynia behavior. All investigated nociception models displayed decreased gnawing behavior. Abstract: Objective: To assess changes in orofacial tactile sensitivity and gnawing related to capsaicin-mediated cutaneous, myogenic, and arthrogenic nociception in the rat. Design: After recovery from anesthesia, orofacial tactile sensitivity and gnawing were assessed using operant testing methods following capsaicin application. Twenty female CD-Hairless rats were tested with bilateral capsaicin cream application to the cheek or with isoflurane anesthesia alone. Following several weeks of recovery, animals (n = 20) received either 10 μL unilateral masseter injections of vehicle, or phosphate buffered saline (PBS) to assess injection sensitization. After several weeks, masseter capsaicin (1.0%) injections (10 μL) were assessed compared to vehicle and PBS (n = 13). Weeks later capsaicin TMJ injections were evaluated. Animals (n = 11) received either 10 μL unilateral TMJ injections of capsaicin solution (1%) or vehicle. Results: Capsaicin cream to the skin significantly altered gnawing activity (increased puncture time by 248 s (p = 0.0002)) and tactile sensitivity (decreased tolerated bottle distance by 0.980 cm compared to isoflurane only (p = 0.0001)). Similarly, capsaicin masseter injection increased puncture time (339.6 s, p = 0.07) and decreased tolerated bottle distance (1.04 cm, p = 0.005) compared to vehicle. However, intra-articular capsaicin in the TMJ only modified gnawing (increased puncture time by 133 s), with no changes found in tactile sensitivity compared to vehicle. Conclusion: Application of capsaicin to the skin and masseter had similar behavioral effects; however, intra-articular injections to the TMJ only affected gnawing. These data indicate the behavioral changes in rodent models of myogenic and cutaneous pain may be markedly different than models of arthrogenic pain originating from the TMJ.